ANALISIS DAMPAK NORMALISASI SUNGAI TERHADAP EROSI DAN SEDIMENTASI DI DAERAH PERKOTAAN STUDI KASUS: SUNGAI PESANGGRAHAN, JAKARTA - Siti Murniningsih; Alfisalam Ghifari Mustafa (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2019)
Flooding is one of the problems that often occurs in the DKI Jakarta area, which one of the causes is the change of land use in watersheds that were originally into development areas. Whereas, its often the cross section of the river will be disrupted due to the loss of the riverbanks and the narrower cross section of the river. In order to overcome this, the Jakarta Provincial Government in 2013 normalized several rivers that crossed the DKI Province and one of them was the Pesanggrahan River which will be further investigated. The purpose of this study is to analyze the effect of river normalization on erosion and sedimentation which will result in changes in the longitudinal and cross section of the river. To get an accurate map of theWatershed Area, Arc-GIS software is used while identification of river flow before and after normalization was carried out based on data from Central Office of River Region Ciliwung-Cisadane, Ministry of Public Works. Sediment samples were taken at 3 points on the river, upstream, middle and downstream, that were reviewed to determine the gradation of the sediment grains. The HEC-RAS application is used to simulate sediment transport on the river section before and after normalization. The simulation results are used to determine the cross section changes due to erosion and sedimentation and to determine the water level in the river. From the water level, the hydraulic radius can be calculated and then carried out sediment transport calculation using Ackers-White equation since the equation using grain distribution from range 0.02 – 4.94 mm. The results it was found that the sediment transport in the upstream point increased 155.11 tons / year,at the midpoint increased 89.64 tons / year and the downstream point decreased 0.28 tons / year.